The Strategic Collaboration of Zeni AD And Penta Helix In Accelerating Infrastructure Development: Case Study Of Trans Papua Road - Supriyanto, Supriyanto (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2024)
Infrastructure development in remote areas, such as Papua, faces significant challenges, including difficult geographical terrain and socio-cultural complexity. Overcoming this challenge requires a collaborative approach involving a wide range of stakeholders. The study aims to analyze the application of the Collaborative Governance and Penta Helix model in accelerating the construction of Papua Trans Road, with a focus on collaboration between the Zeni Army (Zeni AD) and other actors such as the government, the private sector, academics, the community, and the media. The research method used is a qualitative approach to the design of case studies, which involves in-depth interviews, participatory observations, and document analysis. The results show that collaboration through face-to-face dialogue, confidence-building, commitment to processes, and the achievement of temporary results can accelerate the completion of projects and enhance regional independence. The recommendations of this study are to strengthen active participation, local capacity development, transparency, and periodic evaluation in the implementation of future infrastructure projects.